Monday

March 30, 2015

March 30, 2015

Posted by **Abhishek** on Monday, June 4, 2012 at 7:25am.

- Calculus -
**Steve**, Monday, June 4, 2012 at 10:29amy = √(lnx+√(lnx+√(lnx+...)))

y^2 = lnx+√(lnx+√(lnx+...))) = lnx + y

2y y' = 1/x + y'

(2y-1)y' = 1/x

y' = 1/(x(2y-1))

**Answer this Question**

**Related Questions**

math - I tried everthing but,I couldnt solve it. Please help me.the answer at ...

Calculus - Find f'(x) if f(x)= Logx(x^2-5x+6) NOTE: that logx is a sub x

algebra - If LOGx (A)=0.7 and LOGx (B) =0.5 how do I solve LOGx (B/A)

Math - these are some problems i do not get any help is appreciated. These are ...

^Maths^ - If Logx-6 base3=2y and Logx-7 base2=3y, show that x^2-13x+42=72y

maths surds please help and explain - Simplify A.1/root a +2 b.root 18/25 c.root...

pre calculous - solve each equation algebraically and check it by substituing ...

college pre-calculus - simplify: square root (4/3)-square root (3/4) A. 2-...

Algebra - Rationalize each expression by building perfect nth root factors for ...

Calculus I - Find the derivative ** (sq root) y = (square root) x + (2nd sq root...